Innovation and Production in the Global Economy - Arkolakis, Costas; Ramondo, Natalia; Rodríguez-Clare, Andrés; Yeaple, Stephen (American Economic Review, 2018)
We develop a quantifiable general equilibrium model of trade and multinational production (MP) in which countries can specialize in innovation or production. Home market effects or comparative advantage leads some countries to specialize in innovation and relegate manufacturing operations to other countries via outward MP. Counterfactual analysis reveals that the reduction in the cost of MP or the integration of China into the world economy may hurt countries that are driven to specialize in production, although these losses tend to be very small. Contrary to popular fears, production workers gain even in countries that further specialize in innovation. (JEL D58, F12, F14, F23, L60, O31)